Evaluation of phytoconstituent and wound-healing potential of methanolic waste shell extract of Elaeis guineensis Jacquin in female rats - G.V. Awolola; S.S. Emmanuel; A.A. Adesibikan (Elsevier, 2021)
Background: Since historical time, shedloads of Elaeis guineensis Jacquin (Arecaceae family) shells are being treated as waste, and the wasted shells are occasionally used by village herbalists who believe in the superstition working operation of the shell in the treatment of wounds than its therapeutic actions. Purpose: This present study aims to evaluate the phyto-constituents and wound-healing activities of Elaeis guineensis Jacquin methanolic shell extract to objectively establish its therapeutic effectiveness, which was previously misunderstood by village herbalists based on superstition. Study design: The as-prepared methanolic shell extract was subjected to qualitative and quantitative phytochemical analysis. The crude extract was formulated into ointment (5.0, 3.0, and 1.0 g/10 g of ointment base) and applied topically on 40 mm (diameter) excised wound in 5 by 5 groups of rats for 21 days. Methods: The as collected shell waste was washed, dried, pulverized, and subjected to cold maceration for 72 h using methanol. The concentrated extract was analyzed for phytochemicals and then formulated into an ointment by mixing with the melted ointment base. The resulting ointment was applied topically on an excision wound created under diethyl ether anesthetic. The percentage of wound closure was measured in reference to day zero wound area followed by assessment of histological changes. Results: The phytochemical analysis revealed the presence of phenolics, flavonoids, tannins, terpenoids, saponins, and alkaloids, with the phenolics content being the highest (10.4 ± 0.2 g/100 g) while the alkaloids content was the least (0.81 ± 0.03 g/100 g). It was observed that 100% wound healing was found on the 21st day of the experiment in the excision group treated with 3.0/10 and 5.0 g/10 g when compared to the standard group (98.9%) and control group (97.39%). The percentage wound closure of 18.7% on the 3rd day of the experiment was best in the group treated with 5.0 g/10 g of the ointment base, followed by the group treated with 3.0 g/10 g (17.49% wound closure). The histopathological study revealed a significant increase in collagen fibers and fibroblast cells in the group treated with 1.0/10g and 3.0 g/10 g as compared to the standard and the group treated with 5.0 g/10 g that showed cellular necrosis and mild epidermal degeneration on the 21st day of the experiment. Conclusion: Our finding suggests baseline information on the potential use of the waste shell of Elaeis guineensis Jacquin for the treatment and management of wounds in traditional medicine and this is the first report on the use of Elaeis guineensis Jacquin waste shell for wound-healing.